An analysis of the Chinese Football Reform of 2015: why then and not earlier?. Issue 1 (2nd January 2019) - Peng, Qi; Skinner, James; Houlihan, Barrie
ABSTRACT: In March 2015, the Chinese government issued the Overall Plan for Chinese Football Reform and Development, which aimed to develop football in China from the grassroots level to the elite level. The salient element of the plan was to separate the Chinese Football Association (CFA) from direct government control. Considering the previous failed attempts to reform the CFA, this paper asks the question 'why the reform occurred in 2015 and not earlier?' and aims to: 1) identify the potential sources of the policy change through the lens of the Multiple Streams Framework (MSF) and 2) examine the timing and conditions under which the Chinese government initiated the football reform. Public policy documents and media reports from 1993 to 2017 were collected and analysed; 17 interviews were conducted with key policy actors within the CFA and professional football clubs in varying tiers of Chinese football leagues. The findings suggest that the failure of previous policy attempts at improving Chinese football (policy stream), match-fixing scandals and the continuing under-performance of the national men's team (problem stream), the increasingly critical national mood towards football and the turnover of Presidency (political stream) combined in the mid-2010s opened a 'policy window' which facilitated this significant change. This research is the first paper to apply the MSF theory to explain the Chinese football reform that occurred in 2015. It extends the application of MSF to a different political and cultural environment and has implications for the policy-making in China.